Physical activity and sedentary time in children and adolescents with asthma: A systematic review and meta‐analysis. (28th February 2021) - Mackintosh, Kelly A.; McNarry, Melitta A.; Berntsen, Sveinung; Steele, James; Sejersted, Ellen; Westergren, Thomas
Abstract : The influence of asthma on physical activity (PA) in youth remains equivocal. This review synthesizes the evidence regarding the influence of asthma on PA and sedentary time and evaluates the role of key moderators for this relationship. In accordance with PRISMA guidelines, six electronic databases and gray literature were searched. Primary studies in English were included if they reported device‐assessed PA in youth with and without asthma. Random effects meta‐analyses examined the effect of asthma on PA and, separately, sedentary time. Mixed‐effect meta‐regression analyses were conducted using age and sex as moderators, with sub‐group comparisons for study quality and asthma diagnosis criteria. Overall, of 3944 citations retrieved, 2850 were screened after the removal of supplication and 2743 citations excluded. Of the 107 full‐text publications reviewed, 16 were included in data extraction and analysis, with 15 and five studies included in the PA and sedentary time meta‐analyses, respectively. The robust effect size estimate for the influence of asthma on PA and sedentary time was −0.04 [95% CI = −0.11, 0.03] and −0.09 [95% CI = −0.12, −0.06], indicating a non‐significant and significant trivial effect, respectively. The effect of asthma on PA levels or sedentary time was not associated with age or sex. Youth with controlled asthma are equally physically (in)active as their healthy peers, with asthma associated with less sedentary time. However, methodological limitations and a paucity of clear methodological reporting temper these conclusions. More rigorous device‐based assessments, with a particular focus on sedentary time, and more robust diagnoses of asthma, especially with regard to severity, are needed.